'상생'에 기반한 현대 영웅성의 재조명 - 이영준; 김진영; Lee Young-jun; Kim Jin-young (大巡思想論叢, 2024)
Heroes and heroic actions represent the pinnacle of human life. The most noble action that a human can perform is heroism, and throughout history, humanity has bestowed the title of hero upon those who lived such extraordinary lives and then praised them from within that categorization. Traditionally, when discussing heroes, there has always been an archetype of a hero, with a dichotomy of 'I' or 'We' versus an opposing 'other' as an enemy that should be eliminated-whether it be a person or a system. However, in modern times, the archetype of the hero based on sacrifice and opposing forces is undergoing a transformation. This change is due to the recognition of individuals who are acclaimed as heroes without having to inflict harm upon an opponent. If the essential reason why heroes have been praised in human history was for 'saving' someone or something, then the heroes of contemporary society are becoming more closely aligned with the essence of preservation or symbiosis, breaking away from the incidental attributes of destruction or violence, even more so than in the past. In conclusion, heroes are generally conceptualized as positive and pro-social phenomena, and the destructive aspects of heroism, and even its madness, have been largely ignored. Based on the philosophical concept of mutual beneficence (sangsaeng, 相生) in Daesoon Thought, this study will examine the destructive attributes of heroes and then reevaluate the characteristics of heroes from the perspective of saving others. 영웅과 영웅적 행동은 인간 삶의 정점을 나타낸다. 인간이 수행할 수 있는 가장 고귀한 행동이 영웅적 행위(heroism)이며 그런 최고의 삶을 살아간 사람에게 인류는 아낌없이 영웅이라는 칭호를 부여하며 찬사해 왔다. 그런데 전통적으로 영웅을 논할 때는 거의 항상 사람이든, 제도와 같은 유형의 존재이든 제거하거나 소거해야 할 대상으로 대립적 타자의 존재를 당연시 해왔다. '나 또는 우리 대 적(適)'이라는 이분법적 세계관이 영웅의 원형 속에 내재되어 있었다. 그렇지만 현대에 이르러 희생과 대립적 타자를 기반으로 한 영웅의 원형은 변화를 보이고 있다. 누군가를 죽이지 않고도 영웅으로 칭송되는 사람을 적지 않게 발견할 수 있게 되었기 때문이다. 영웅이 인류 역사에서 칭송이 된 본질적인 이유가 '살림'이었다면, 현대 사회의 영웅은 과거보다도 온전하게 그 원형에 있어서 파괴나 폭력이라는 부차적 속성에서 벗어나 '살림', 즉 상생이라는 본질에 더 가까워지고 있는 것이다. 결론적으로, 영웅은 일반적으로 긍정적, 친사회적 현상으로 개념화되어 영웅과 영웅 숭배의 파괴적 측면, 더 나아가 광기는 도외시되었다. 이에 본 연구는 해원상생의 대순사상을 토대로 영웅의 파괴적 속성을 살펴보고 현대의 변화하는 영웅상을 기초로 증산이 추구하자고 했던 상생으로서 '살림'의 측면에서 영웅의 특성을 재검토할 것이다.